Variasi Heat Treatment dalam Meningkatkan Sifat Mekanik Pahat Bubut HSS di Laboratorium Teknik Pemesinan - Yopi Yogasmana; Mutaufiq Mutaufiq; Rensinna Ilmiwar Chair (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
The workpiece is shaped into a gear/shaft/hammer by cutting it with a lathe chisel while the lathe rotates at high speed. ST37 steel, a low-carbon steel, can be cut by a high-carbon steel lathe chisel. However, in reality, some lathe chisels are unable to cut ST37 steel, which is indicated by wear and even fracture at the cutting angle of the lathe chisel. The purpose of this research is to improve the mechanical properties of HSS lathe tools to make them harder and more durable. The method used in this research is an experiment by giving heat treatment at three different temperature variations: 780°C, 800°C, and 850°C. After the heat treatment, the hardness and toughness were tested.The results of the hardness test on the HSS lathe tool before heat treatment were 56.4 HRC and after heat treatment were 39.3 HRC; 39.0 HRC and 61.7 HRC. The results of the impact test on the HSS lathe tool before heat treatment were 2.8 Joules/mm2 and after heat treatment were 5.1 Joules/mm2; 4.7 Joules/mm2 and 3.7 Joules/mm2. Heat treatment variations at a temperature of 850°C with a holding time of 25 minutes and quenching with oil media resulted in an increase in hardness value of 5.3 HRC and an increase in toughness value of 0.9 Joules/mm2.